(untitled) (Epidemiology, Biostatistics, and Public Health, 2025)
BACKGROUND Gynecological conditions significantly impact emotional well-being, relationships, and overall quality of life, alongside presenting medical challenges [1]. Anxiety, depression, and stress due to concerns about diagnosis, treatment, and body image, are now widely recognized as critical determinants of health [2-5]. Additionally, patients often face social challenges such as financial instability, limited healthcare access, and social isolation, which exacerbate distress [6]. Some studies have examined the social needs experienced by patients with gynecological disorders, but primarily in gynecologic oncology patients [2,7-9]. OBJECTIVES This study aims to assess the prevalence of distress among patients attending at an Italian tertiary gynecological clinic while also exploring socio-demographic, psychological, clinical, and lifestyle factors influencing distress, violence, and food insecurity. METHODS This prospective cross-sectional study received local ethical approval (Prot. N. 10524/23) to enroll women attending the Gynaecological Outpatient Clinic of Fondazione Policlinico A. Gemelli IRCCS in Rome, Italy. From March to November 2023, an ad-hoc questionnaire, was administered by trained volunteers to all eligible women (≥18 years old) seeking gynecological care, excluding those unable to provide consent due to mental disorders. All volunteers were women members of the Associazioni Cristiane Lavoratori Italiani (Acli Roma APS), a national society for social promotion and had at least four years of experience in social projects. The questionnaire was validated through a Delphi procedure involving eight multidisciplinary experts and comprised 42 questions covering socio-demographics, family situation, clinical history, socio-psychological distress, and lifestyle. Responses were analysed focusing on three key outcomes among women: socio-psychological distress, violence experienced and food insecurity. Inferential analysis was performed including multivariable logistic regression models incorporating statistically significant parameters from univariable analysis. Estimates were reported as Odds Ratios (OR) with 95% Confidence Intervals (CI). The analyses were conducted using STATA software, with a significance level of p = 0.05, adjusted using Bonferroni’s correction where needed. RESULTS 408 women were included in the study. 45.6% of patients attended the gynecological outpatient clinic for benign conditions, 38.5% for oncological issues, and 18.6% for preventive check-ups. Over 64.0% underwent medical or surgical treatment, and nearly half (47.1%) had a chronic disease. Sociodemographic findings showed that 97.1% of patients were Italian, primarily from central Italy. Almost half were married or in stable relationships, with 19.4% holding postgraduate degrees and 53.9% employed full-time. 152 (37.2%) reported socio-psychological distress, 136 (33.3%) violence, and 60 (14.7%) food insecurity. About 50% of women reported that the disease had changed their lives, both in terms of self-perception and relationships with others. Additionally, 34.6% reported that people’s attitudes toward them had changed because of the disease. Multivariable analysis shown in Table1 identified oncological disease, chronic conditions, economic difficulties, and experiencing violence as independent risk factors for socio-psychological distress. Experiencing violence was associated with benign gynecological conditions, alcohol use, economic struggle, and experiencing food insecurity. Economic difficulties were the strongest independent predictor of food insecurity. CONCLUSION Socio-psychological distress and experiences of violence were found to be prevalent in over one-third of the studied population, highlighting the urgent need for integrated social support systems within gynecologic healthcare - especially for individuals facing economic hardship and food insecurity. A promising intervention could be trained volunteers specializing in social care, addressing both psychological and social health determinants to enhance patient well-being and overall outcomes through holistic interventions.